Cancer Genomics and Patient-Specific Treatment Modalities - Muhammad Akram; Jehan Mohammed; Abid Mahmood Abid Mahmood; SOONMIN HO; Hanine Hadni Hanine Hadni (Public Health of Indonesia, 2026)
Background: Cancer genomics and personalized treatment approaches aim to provide better treatment by understanding the individual genetic profile of each patient. This increases the effectiveness of drugs, prevents unnecessary treatment, and improves recovery rates. This leads to tailored therapies and better outcomes. The most important developments that will shape the future of cancer research and drug discovery are presented in this article. Sequencing of next-generation and other technologies allows for complete genomic profiling to identify and target actionable mutations. By going beyond traditional chemotherapy, researchers can develop more potent and less toxic drugs by identifying the unique mutations at the root of each patient's cancer. By inhibiting the brakes of the immune system, these drug T cells allow cancer cells to attack more effectively. Objectives: To study different types of treatments that could be used to improve patient stratification, optimize clinical trials, and personalize treatment plans using real-world data. Methods: Data were analyzed from journal articles in Google Scholar, MDPI, Web of Science, Scopus and Science Direct, from 2002 to 2025. Results: Several goals of tumor microenvironment elements, such as extracellular matrix and immune cells living in TME, offer potential for new therapeutic strategies. A huge amount of genetic data was evaluated, future medical prospects were discovered, and outcomes for patients with AI programs were predicted. Additionally, machine learning algorithms are used to solve this problem. Due to the complexity and versatility of cancer, combination treatments with several mechanisms of action and several mechanisms of action are becoming more common. To maximize efficacy with targeted therapies, chemotherapy, radiation therapy, and other modalities. The goal is to prevent tumor cells from being treated by targeting cancer from several directions. These combinations are currently being tested in clinical studies, showing promising results, particularly for cancers such as breast, lung, and melanoma. Conclusion: Cancer genomics and personalized medicine are major advances in modern medicine. They have led to significant improvements in diagnosis accuracy, treatment, and outcomes. By adapting treatment to the patient's genetic profile, greater therapeutic benefit and fewer side effects can be achieved, promoting a healthier life.